(untitled) (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines legal protection for investors who suffer unlawful losses due to insider trading in the Indonesian capital market. The issue is important because trading based on non-public material information distorts the principle of disclosure, undermines market fairness, and places ordinary investors in a structurally disadvantaged position. Using normative juridical research with statutory and case-based support, the article reviews Law Number 8 of 1995 on Capital Markets and Financial Services Authority Regulation Number 65/POJK.04/2020 on disgorgement and investor compensation. The study finds that investor protection under the Capital Market Law operates through preventive and repressive mechanisms, including supervision, disclosure obligations, inspection authority, and administrative or civil sanctions. However, proof of insider trading remains difficult, especially when information moves through indirect recipients or informal channels. The article concludes that POJK Number 65/POJK.04/2020 strengthens legal certainty by creating a mechanism to recover unlawful gains and compensate harmed investors, but more detailed standards on insider categories, material information, and enforcement coordination are still needed.